Elements For a Synergetic Approach to Peirce’s Semiotics and Adamczewski’s Linguistics - Cosculluela, Cécile (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2009)
How legitimate is the use of numbers by linguistic operators zero, phase 1 and phase 2? It seems that these references to the philosophy of mathematics pose a problem that is inherently tied to the core of the science of linguistics. The Peircean categories of firstness, secondness and thirdness not only offer terminogical solutions, but also corollary epistemological openings that allow for the substitution of linguistic’s empiricism by a semiotic basis.